Competitividade e caracterização genética de Conyza bonariensis ocorrentes no Estado do Rio Grande do Sul - Silva, Diecson Ruy Orsolin da (2013)
Conyza bonariensis (hairy fleabane) is the main glyphosate resistant weeds on soybean crops in Rio Grande do Sul State. The herbicide resistant weeds may have modified their competitive ability, due to the ability to resist the action of the herbicide. Knowledge of weed competitive ability allows us to adopt the best management strategies to improve the crops, without incurring economic losses for farmers. The study aimed to evaluate the competitiveness of biotypes of hairy fleabane in soybean; determine the interference of control periods and coexistence; assess the crop yield loss and the threshold level of glyphosate resistant hairy fleabane biotypes on soybeans; photosynthetic responses between glyphosate resistant and susceptible biotypes; determine changes in photosynthesis and accumulation of shikimic acid in hairy fleabane biotypes under glyphosate effect, and characterize the hairy fleabane diversity occurring in Rio Grande do Sul State. The experimental results show that the cultivar CD 226 RR has a lower competitive ability that hairy fleabane biotypes, and susceptible biotype is more damage to soybean, soybean has a higher oxidative stress when in competition with resistant biotype; cultivar BRS Estância RR has greater competitive ability than horseweed regardless of stage of development, and soy does not suffer from competition for resources of soil, light or both. The Increasing coexistence periods of hairy fleabane with soybean affect the physiological and morphological responses of crop. And the increase in hairy 10 fleabane population impacts negatively crop yield and is more economical control hairy fleabane plants when allocating a greater population. The glyphosate resistant hairy fleabane biotype has better adaptability photosynthetic compared with the glyphosate susceptible population. The effect of glyphosate on the hairy fleabane biotypes is most intense on the glyphosate susceptible biotype, reducing growth and inhibiting completely the photosynthesis variable and EPSPs enzyme. RAPD analysis can be important tool for characterization Conyza species.